2009
DOI: 10.1103/physrevb.79.174435
|View full text |Cite
|
Sign up to set email alerts
|

Tweaking the spin-wave dispersion and suppressing the incommensurate phase inLiNiPO4by iron substitution

Abstract: Elastic and inelastic neutron-scattering studies of Li͑Ni 1−x Fe x ͒PO 4 single crystals reveal anomalous spinwave dispersions along the crystallographic direction parallel to the characteristic wave vector of the magnetic incommensurate phase. The anomalous spin-wave dispersion ͑magnetic soft mode͒ indicates the instability of the Ising-type ground state that eventually evolves into the incommensurate phase as the temperature is raised. The pure LiNiPO 4 system ͑x =0͒ undergoes a first-order magnetic phase tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
23
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
6
23
0
1
Order By: Relevance
“…We thus confirm earlier results obtained by neutron diffraction: 35 A substitution of 6% is too small for exerting fundamental changes in the magnetic structure. The magnetic properties of (iv) The data point to an unusually large single-ion anisotropy of the Fe 2+ ions which is consistent with other observations on the LiMPO 4 system.…”
Section: Nn Inter-plane Coupling Along a Is Of The M-o-p-o-m Type Andsupporting
confidence: 81%
See 2 more Smart Citations
“…We thus confirm earlier results obtained by neutron diffraction: 35 A substitution of 6% is too small for exerting fundamental changes in the magnetic structure. The magnetic properties of (iv) The data point to an unusually large single-ion anisotropy of the Fe 2+ ions which is consistent with other observations on the LiMPO 4 system.…”
Section: Nn Inter-plane Coupling Along a Is Of The M-o-p-o-m Type Andsupporting
confidence: 81%
“…This is in agreement with experiments on LiMnPO 4 where a Fe substitution of 30% (or less) achieves this purpose. 44 Furthermore, the Fe substitution readily suppresses the incommensurate magnetic phase of LiNiPO 4 with spin rotation in the yz plane 21,35 which is also consistent with a dominating Fe 2+ single-ion anisotropy.…”
Section: Nn Inter-plane Coupling Along a Is Of The M-o-p-o-m Type Andsupporting
confidence: 57%
See 1 more Smart Citation
“…4,5 The LiNiPO 4 compound exhibits the exceptionally large ME coefficients and the hysteresis of the "butterfly" type at low temperature. [7][8][9] Neutron scattering studies have shown that the spin system associated with the Ni 2+ ions in this single crystal LiNiPO 4 undergoes a commensurateincommensurate ͑IC͒ magnetic phase transition near Néel temperature. Olivine LiNiPO 4 crystallizes in the Pnma space group, and consist of distorted NiO 6 , LiO 6 , and PO 4 units.…”
mentioning
confidence: 90%
“…[1][2][3] In the olivine phosphate materials, LiMPO 4 ͑M =Ni,Fe,Co,Mn͒, a strong magnetoelectric ͑ME͒ effect has been observed in the antiferromagnetic ͑AF͒ phases. [6][7][8] The NiO 6 octahedra is cornershared and cross-linked with the PO 4 tetrahedra, forming a three-dimensional network, with tunnels along the ͓010͔ and ͓001͔ directions occupied by Li ions. A general mechanism leading to this ME effect in LiNiPO 4 has not yet been established.…”
mentioning
confidence: 99%